Complication trends in gynecologic endoscopy: a global registry review - Manchanda, Rahul; Gupta, Ruchika; Arunaa, Roshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Minimally invasive gynecologic surgery (MIGS) has expanded substantially over the past decade, supported by technological advances, structured surgical training, and enhanced perioperative care pathways. Although MIGS offers clear benefits over laparotomy, clinically significant complications—including vascular, bowel, and urinary tract injuries in laparoscopy and uterine perforation, fluid overload, and gas embolism in hysteroscopy—remain important contributors to morbidity. Earlier literature, primarily derived from single-centre retrospective studies, was limited by inconsistent definitions and incomplete reporting, prompting greater reliance on national and multinational registries to capture real-world outcomes. This narrative review synthesises evidence from registry analyses, large administrative databases, and institutional audits published between 2015 and 2025 to evaluate complication patterns, risk factors, and prevention strategies in gynecologic laparoscopy and hysteroscopy. Across datasets, advanced age, elevated BMI, prior abdominal surgery, high ASA class, prolonged operative duration, and increased procedural complexity consistently emerged as risk factors. Preventive measures—including structured skills training, simulation-based crisis preparation, intraoperative monitoring standards, device- and technique-specific safeguards, and ERAS-based perioperative protocols—were associated with improved safety. Despite these gains, substantial heterogeneity persists in complication definitions, follow-up intervals, coding standards, and case-mix adjustment across registries, contributing to under-reporting and limiting meaningful international benchmarking. Harmonised reporting frameworks, unified definitions, minimum dataset requirements, and integrated cross-disciplinary reporting structures are essential to improving surveillance, guiding training and credentialing, and strengthening global quality-improvement efforts in gynecologic endoscopy.